EXPERIENCE IN IMPLEMENTING PRACTICE-ORIENTED MODEL FOR STUDENTS TRAINING IN INNOVATIVE ENTREPRENEURSHIP - Nikolay A. Shapovalov; Ludmila G. Romanovich; Evgeny S. Glagolev; Alexandr N. Babaevski (Moscow Polytechnic University, 2016)
The article discusses topical issues of implementation of practice-oriented model of students' training in innovative entrepreneurship on the basis of higher education institutionsof Russia. The authors present and analyze the positive experience of Belgorod State Technological University named after V.G. Shukhov, which dynamically develops effective model of educational research and innovation complex, providing incentives for innovation activities of young scientists and commercialization of university intellectual property. In this paper, by the example of the project «Production of composite binding» there are examined the stages of creating industrial enterprise with implementing the innovations of the University. The specificity of organization of innovative youth activities may be of interest both for Russian and foreign organizations and partners.